Effectiveness of English Tutorial Video on Youtube in Improving Speaking Fluency: Effectiveness of English Tutorial Video on Youtube in Improving Speaking Fluency - Towanga, Doni K N Towanga; Liando, Nihta V. F; -, Ismail (Program Studi Pendidikan Bahasa Inggris, 2025)
Speaking fluency is the ability to express thoughts, ideas, and feelings smoothly and coherently through spoken language. It is a fundamental skill that encompasses not only the act of speaking but also the capacity to communicate effectively. To express ideas clearly, one must possess focus, retain relevant information, and have a solid understanding of the topic being discussed. However, many students often face challenges in improving their speaking fluency. As a result, researchers and educators have increasingly turned to YouTube video tutorials as a supplementary tool in foreign language instruction. This study aims to determine the effectiveness of YouTube video tutorials in enhancing students' speaking fluency. The research employs a single-group pre-test and post-test design using a quantitative approach. A total of 20 eleventh-grade students from SMA Negeri 2 Tondano participated as the research sample. Pre-tests and post-tests were administered as instruments for data collection. The findings indicate a significant improvement in students' speaking fluency, with the average score increasing from 56.00 in the pre-test to 82.25 in the post-test. These results suggest that YouTube video tutorials can effectively enhance students’ English-speaking fluency, train their comprehension skills, and increase their motivation to learn foreign languages. However, the effectiveness of YouTube as a learning tool is influenced by several factors, including students’ learning proficiency and the ability of teachers or instructors to deliver lessons effectively.